UNIVERSALISME ISLAM DAN ISLAM LOKAL: KAJIAN PERBANDINGANNYA - Endang Switri; Ris’an Rusli; Anisatul Mardiah (Raudhah - Proud To Be Professional, 2023)
Abstract, This scientific work discusses the universalism of Islam and local Islam as well as comparative studies between Islamic universalism and local Islam. Islam is a religion of Rahmatan Lil'alam, of course, it does not distinguish one from another. The method in writing scientific works is the library method. Then this scientific work shows that Islamic universalism or Islam universalism, gentle Islam, friendly Islam, mingling Islam and love for the world including people of different religions, but there are limitations in terms of four so that Islam can grow and share in life. (From a social perspective), while local Islam is Islam that develops and grows in certain areas/regions, and the specific development of Islam in an area/region is different because each region has different cultures.